Implementasi Pendekatan Andragogi Spiritual dalam Meningkatkan Motivasi Belajar Mandiri Mahasiswa pada Program Studi Pendidikan Bahasa Indonesia FKIP Universitas Muhammadiyah Banjarmasin - Jamiatul Hamidah; Akhmad Syakir (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2021)
Lecture methods carried out by lecturers greatly affect the results that will be achieved by students, whether it includes the teaching and learning process, assignments, and during exams. The spiritual andragogy approach gives freedom to students to grow independent learning, awareness of self-potential development, and motivation to achieve learning goals. This study aims to describe the application of a spiritual andragogy approach in lectures to optimize student learning outcomes. This study uses a descriptive method with a qualitative approach. The method used in data collection is interviews and the distribution of open questionnaires to lecturers and students. Sources of data were obtained from 40 students and 6 lecturers at the Indonesian Language Education Study Program, FKIP, University of Muhammadiyah Banjarmasin. The results showed that the application of a spiritual andragogy approach could improve student motivation and learning outcomes. The spiritual andragogy approach is a learning approach for adults that emphasizes the spirit or psychology of students at the adult level. In the Indonesian Language Education Study Program, the application of this approach is carried out in various aspects based on the inculcation of the values ​​of Al-Islam Kemuhammadiyahan. The application is carried out by lecturers starting from learning preparation, the process of learning activities, to assessment or evaluation activities.